Prevalence of Rotavirus among Iraqi Children with Diarrhea in Diyala Province - Hameed, Ali R.; Mohamed, Bakri Y.; Abakar, Adam D.; Ali, Karim S. (International Journal of Scientific Research in Biological Sciences, 2021)
In children under the age of five, rotavirus is the leading cause of acute gastroenteritis. The aim of this study was to see how common rotavirus is in children who have diarrhea, the efficacy of Immuno Chromatography Assay (ICA) and Enzyme-linked Immunosorbent assay (ELISA) and evaluate the relationship between the demographic agent and clinical presentation associated with rotavirus. At AL-Batool Teaching Hospital in Baqubah, a cross-sectional study was conducted, from the first of April 2019 to 31 of March 2020, on (300) children with diarrhea below five years of age. The patients included (n=161, 53.6%) males and (n=139, 46.3%) females. The patient’s age, gender, living area, season, mode of feeding, source of water supply and sterilization, were gathered using a questionnaire designed specifically for this study. Rotavirus is detected in fecal specimens using the ICA and ELISA tests. The rotavirus antigen was detected in (47.33%) stool specimens by the ELISA test and (59%) by ICA from (300) children with diarrhea and high infection in the age group between 13-24 months at the rate (49.40%). The highest infection rate in spring was (56.00%) and lower in summer (33.33%). Males were infected at a higher rate than females (42.24% vs. 39. 57%).High significant infection among children living in rural areas (55.68%) compared to those living in urban areas (35.48%). According to the clinical features, the findings revealed the prevalence of rotavirus infection in children who had a fever (54.90%), vomiting (42.03%), those suffering from severe dehydration (48.85) some dehydration 78 (46.15%). However, rotavirus infection was significant with fever only.